ANALISIS POLA KONSUMSI PANGAN DAERAH PERKOTAAN DAN PEDESAAN SERTA KETERKAITANNYA DENGAN KARAKTERISTIK SOSIAL EKONOMI DI PROVINSI KALIMANTAN TIMUR - Sari, Nilam Anggar (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2016)
This study aimed to analyze the interaction of socio economic characteristics in influencing patterns of food consumption by the typology of the area (rural and urban) and educational level of household head how the response changes in food consumption of households as a result of changes in prices and income (elasticity) that occurred in East Kalimantan Province.The analytical method used is descriptive and econometric analysis uses data Susenas 2015 with Linear Approximation of Almost Ideal Demand System models (LA / AIDS) were estimated by the Seemingly Unrelated Regression (SUR) through the procedure of Generalized Least Square (GLS). The author conducted data aggregation to overcome bias selectivity using instrumental variables to address the simultanity bias price, quality effect and quantity premium. It also conducted a restriction symmetry, homogenity and adding-up in order to function in accordance with the theory of demand.In general, commodity prices have a significant effect on the level of consumption of commodity groups, although there are some variables that are not significant. Revenues proxy for general expenses are all significantly influence the level of consumption of food commodity groups. Generally, socio economic characteristics influence significantly affect the level of consumption, although there are some that are not significant. In general, the age of  household head and the number of families does not significantly influence the level of household consumption. All commodity groups in general are normal goods and almost all commodity groups included in the category of necessities goods, except food groups of vegetables / fruits and cigarette groups are considered as luxury goods.Keywords: LA-AIDS,  Elasticity, Rural, Urban, Socio Economic Characteristic